Implications of high-dose vitamin D3 with and without vitamin C on bone mineralization and blood biochemical factors in broiler breeder hens and their offspring - Kianfar, Ruhollah; Kanani, Reza; Janmohammadi, Hossein; Olyaee, Majid; Besharati, Maghsoud; Lackner, Maximilian (PeerJ, 2025)
As broiler breeder hens age, they often experience a decline in bone mineralization and calcium absorption, especially during the later stages of egg production. This issue not only affects the hens’ health, making them more prone to conditions like osteoporosis, but it also impacts the quality of their offspring. To tackle this problem, our study explores whether supplementing these hens with a combination of vitamins D3 and C could help improve their bone health and overall biochemical balance, both for them and their progeny. The goal of this research was to evaluate the effects of high doses of vitamin D3, with and without added vitamin C, on bone mineralization and key blood parameters in aging broiler breeder hens and their offspring. In this experiment, 240 hens and 24 roosters from the Ross 308 strain, aged between 49 and 61 weeks, were used, and a two-way ANOVA (2 × 2) design was applied. This involved two levels of vitamin D3 (3,500 IU and 5,500 IU) and two levels of vitamin C (0 and 150 mg/kg), with six replications of 10 hens and one rooster per group. At the end of the study, blood samples were collected from hens and their offspring for biochemical analysis, and tibia bones were taken for ash content and mineralization assessment. The findings showed that vitamin D3 supplementation significantly lowered blood cholesterol, alkaline phosphatase (ALP), and parathyroid hormone (PTH) levels (P < 0.05), while boosting calcium, 25-hydroxycholecalciferol (25(OH)D3), and 1,25-dihydroxycholecalciferol (1,25(OH)2D3) (P < 0.05). Higher doses of vitamin D3 also improved the strength, resistance, and ash content of the hens’ tibia bones, and increased calcium in the carcasses of their offspring. Adding 150 mg/kg of vitamin C to the diet also had a positive effect, reducing cholesterol, ALP, and PTH, while enhancing plasma calcium, total antioxidant capacity, and the active form of vitamin D3 (P < 0.05). Vitamin C supplementation significantly strengthened the tibial bones of the hens and improved plasma calcium and PTH levels in their offspring (P < 0.05). Interestingly, combining elevated doses of both vitamins D3 and C resulted in even greater improvements in tibial bone strength (P < 0.05). In conclusion, giving hens 150 mg of vitamin C along with 5,500 IU of vitamin D3 leads to substantial improvements in the calcium content and structural integrity of their bones, and also boosts calcium and ash content in the carcasses of their offspring.
Keywords: Bone mineralization; Broiler breeder hens; Vitamin C; Vitamins D3